2019
DOI: 10.1038/s41467-019-13178-2
|View full text |Cite
|
Sign up to set email alerts
|

A sodium-ion sulfide solid electrolyte with unprecedented conductivity at room temperature

Abstract: Solid electrolytes are key materials to enable solid-state rechargeable batteries, a promising technology that could address the safety and energy density issues. Here, we report a sulfide sodium-ion conductor, Na2.88Sb0.88W0.12S4, with conductivity superior to that of the benchmark electrolyte, Li10GeP2S12. Partial substitution of antimony in Na3SbS4 with tungsten introduces sodium vacancies and tetragonal to cubic phase transition, giving rise to the highest room-temperature conductivity of 32 mS cm−1 for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
295
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(314 citation statements)
references
References 27 publications
7
295
0
2
Order By: Relevance
“…Similar observations of increased conductivity upon pressing were found from recent variable-pressure conductivity measurements on the isostructural Na3SbS4 44 . These observations are analogous to variations of measured ionic conductivity as a function of pellet preparation which has been reported for several solid electrolytes [64][65][66] , including ball-milled Na3PS4 56 . We attribute this to extrinsic effects on macroscopic ionic percolation through the consolidation of the pellet, improving particle-particle and pellet-electrode contact.…”
Section: Micro- Average-and Local Structures Of Ht-and Bm-na3ps4 Sysupporting
confidence: 85%
See 1 more Smart Citation
“…Similar observations of increased conductivity upon pressing were found from recent variable-pressure conductivity measurements on the isostructural Na3SbS4 44 . These observations are analogous to variations of measured ionic conductivity as a function of pellet preparation which has been reported for several solid electrolytes [64][65][66] , including ball-milled Na3PS4 56 . We attribute this to extrinsic effects on macroscopic ionic percolation through the consolidation of the pellet, improving particle-particle and pellet-electrode contact.…”
Section: Micro- Average-and Local Structures Of Ht-and Bm-na3ps4 Sysupporting
confidence: 85%
“…Multiple hypotheses have been proposed including atomic-scale changes in crystal structure and/or in point defect concentrations, microstructural effects (such as grain boundaries), as well as mesostructural parameters such as particle size/shape and associated surface effects 18,22,23 . Both simulations and experiments show that introducing sodium ion defects through aliovalent doping can decisively enhance ion-transport in Na3PS4 9,11,13,[24][25][26][27][28][29][30] . Through novel atomistic simulations, the effect of grain boundaries on ion conduction in β-Na3PS4 has recently been examined 31 , showing that ion transport is not significantly affected by grain boundaries in this material in contrast to sodium phosphate analogues.…”
Section: Introductionmentioning
confidence: 97%
“…It should be noted that after the completion of this study a considerably higher ionic conductivity of 32 mS cm À1 has just been reported in highly W-doped Na 3 SbS 4 . 39,40 Despite the structural similarities to Na 3 SbS 4 , tetragonal Na 4 SnS 4 (space group P42 1 c) is practically insulating with an ionic conductivity o10 À4 mS cm À1 . 41 Inspired by the then record high conductivity of LGPS 3 and the related Li 10 MP 2 S 12 family of compounds (M = Ge, Si, Sn) [7][8][9][10][11] the existence of isostructural Na 10 MP 2 S 12 (M = Si, Ge, Sn) was predicted by first-principle calculations as metastable phases with the same tetragonal space group P4 2 /nmc adopted by LGPS.…”
Section: Introductionmentioning
confidence: 99%
“…Reprinted and adapted from Ref. [257] under a Creative Commons Attribution 4.0 International License. (b) Comparison of voltage profiles for MoS 2 as electrode in sodium and lithium solid-state batteries with Na 3 PS 4 and Li 3 PS 4 as solid electrolytes and Sn-Na and as negative electrodes respectively (room temperature).…”
Section: All Solid-state Sodium Batteriesmentioning
confidence: 99%